The interaction between artemether-lumefantrine and lopinavir/ritonavir-based antiretroviral therapy in HIV-1 infected patients. Issue 1 (December 2015) - Kredo, T.; Mauff, K.; Workman, L.; Van der Walt, J.; Wiesner, L.; Smith, P.; Maartens, G.; Cohen, K.; Barnes, K.
Abstract Background Artemether-lumefantrine is currently the most widely recommended treatment of uncomplicated malaria. Lopinavir–based antiretroviral therapy is the commonly recommended second-line HIV treatment. Artemether and lumefantrine are metabolised by cytochrome P450 isoenzyme CYP3A4, which lopinavir/ritonavir inhibits, potentially causing clinically important drug-drug interactions. Methods An adaptive, parallel-design safety and pharmacokinetic study was conducted in HIV-infected (malaria-negative) patients: antiretroviral-naïve and those stable on lopinavir/ritonavir-based antiretrovirals. Both groups received the recommended six-dose artemether-lumefantrine treatment. The primary outcome was day-7 lumefantrine concentrations, as these correlate with antimalarial efficacy. Adverse events were solicited throughout the study, recording the onset, duration, severity, and relationship to artemether-lumefantrine. Results We enrolled 34 patients. Median day-7 lumefantrine concentrations were almost 10-fold higher in the lopinavir than the antiretroviral-naïve group [3170 versus 336 ng/mL;p = 0.0001], with AUC(0-inf) and Cmax increased five-fold [2478 versus 445 μg.h/mL;p = 0.0001], and three-fold [28.2 versus 8.8 μg/mL; p < 0.0001], respectively. Lumefantrine Cmax, and AUC(0-inf) increased significantly with mg/kg dose in the lopinavir, but not the antiretroviral-naïve group. While artemether exposure was similar between groups, Cmax and AUC(0-8h) of its active metabolite dihydroartemisinin were initially two-fold higher in the lopinavir group [p = 0.004 andp = 0.0013, respectively]. However, this difference was no longer apparent after the last artemether-lumefantrine dose. Within 21 days of starting artemether-lumefantrine there were similar numbers of treatment emergent adverse events (42 vs. 35) and adverse reactions (12 vs. 15, p = 0.21) in the lopinavir and antiretroviral-naïve groups, respectively. There were no serious adverse events and no difference in electrocardiographic QTcF- and PR-intervals, at the predicted lumefantrine Tmax . Conclusion Despite substantially higher lumefantrine exposure, intensive monitoring in our relatively small study raised no safety concerns in HIV-infected patients stable on lopinavir-based antiretroviral therapy given the recommended artemether-lumefantrine dosage. Increased day-7 lumefantrine concentrations have been shown previously to reduce the risk of malaria treatment failure, but further evidence in adult patients co-infected with malaria and HIV is needed to assess the artemether-lumefantrine risk : benefit profile in this vulnerable population fully. Our antiretroviral-naïve patients confirmed previous findings that lumefantrine absorption is almost saturated at currently recommended doses, but this dose-limited absorption was overcome in the lopinavir group. Trial registration Clinical Trial Registration numberNCT00869700 . Registered on clinicaltrials.gov 25 March 2009